SWOT Analysis of Laundry Business in Jakarta, Indonesia - Tarigan, Emenina; Swantari, Anita; Purwanti Dyah Pramanik, (International Journal of Scientific Research and Management (IJSRM), 2025)
This study aims to analyze the strengths, weaknesses, opportunities, and threats (SWOT) that affect the development of laundry businesses in Jakarta as one form of micro and small businesses that are growing rapidly in urban areas. The approach used is descriptive qualitative with data collection techniques through semi-structured interviews with laundry business owners and managers in five areas of DKI Jakarta. Data were analyzed using the IFAS and EFAS matrices to identify internal and external factors, which were then formulated into a SWOT matrix as the basis for development strategies. The results of the study indicate that the main strengths of laundry businesses lie in their strategic locations, pick-up and delivery services, and trained workers, while their weaknesses include limited capital, manual equipment, and suboptimal digital marketing. On the external side, opportunities such as government support and the development of digital technology can be utilized to overcome threats such as business competition and regulatory uncertainty. The conclusion of this study shows that the ST (Strength-Threat) and WT (Weakness-Threat) strategies are dominant strategies that need to be implemented. It is recommended that business actors adopt digital innovation, increase production capacity, and strengthen business networks to face competitive and sustainable market dynamics.